Phytocompounds and in vitro antiaging activity of ethanolic extract and fractions of Rubus fraxinifolius Poir. leaves - Sulistyowati; Berna Elya; Raditya Iswandana; Syamsu Nur (GarVal Editorial Ltda., 2023)
Context: The leading cause of skin sunburn is exposure to ultraviolet radiation (UVR), which can also cause reactive oxygen species (ROS), which accelerates aging. Rubus fraxinifolius Poir. leaf ethanolic extract may have antiaging properties by preventing elastase enzyme activity. Aims: To compare the antioxidant activity and elastase enzyme inhibition from old and young leaves using Soxhlet extraction and evaluate the antioxidant activity and elastase enzyme inhibition utilizing a variety of extraction techniques, including conventional Soxhlet extraction and unconventional methods like microwave-assisted extraction (MAE) and ultrasonic-assisted extraction (UAE). Methods: Using various extraction methods, samples were extracted with 96% ethanol (Soxhlet, MAE, and UAE). The active extract was then transformed into n-hexane, ethyl acetate, and distilled water fraction. Following the total phenolic and total flavonoid content analysis, the antioxidant activity was evaluated using the radical scavenging tests of 1,2-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power assay (FRAP), and ABTS radicals, or 2,2'-azino-bisphenol S (2,2'-ABPS) (3-ethylbenzothiazoline-6-sulphonic acid). The antiaging potential of skin breakdown enzymes was examined using elastase. Results: According to the R. fraxinifolius leaf's optimization type, extract from older leaves performs better than from younger leaves in terms of antioxidant activity and elastase enzyme inhibitory activity. In terms of optimization extraction, UAE approaches to produce the best outcomes than Soxhlet and MAE. Additionally, using the chosen UAE extraction method, multilayer fractionation was done using n-hexane, ethyl acetate, and distilled water solvents, with distilled water fraction producing the best results. Conclusions: The distilled water fraction from R. fraxinifolius leaf's shows the potential for future research to support its efficacy as an active component in antiaging cosmetics.